Views of healthcare professionals about the role of active monitoring in the management of ductal carcinoma in situ (DCIS): Qualitative interview study. (December 2020) - Nickel, Brooke; McCaffery, Kirsten; Houssami, Nehmat; Jansen, Jesse; Saunders, Christobel; Spillane, Andrew; Rutherford, Claudia; Dixon, Ann; Barratt, Alexandra; Stuart, Kirsty; Robertson, Geraldine; Hersch, Jolyn
Abstract: Background: Ductal carcinoma in situ (DCIS) is an in-situ (pre-cancerous) breast malignancy whereby malignant cells are contained within the basement membrane of the breast ducts. Increasing awareness that some low-risk forms of DCIS might remain indolent for many years has led to concern about overtreatment, with at least 3 clinical trials underway internationally assessing the safety of active monitoring for low-risk DCIS. This study aimed to understand healthcare professionals' (HCPs) views on the management options for patients with DCIS. Methods: Qualitative study using semi-structured interviews with HCPs involved in the diagnosis and management of DCIS in Australia and New Zealand. Interviews were audio-recorded, transcribed and analysed thematically using Framework Analysis method. Results: Twenty-six HCPs including 10 breast surgeons, 3 breast physicians, 6 radiation oncologists, and 7 breast care nurses participated. There was a strong overall consensus that DCIS requires active treatment. HCPs generally felt uncomfortable recommending active monitoring as a management option for low-risk DCIS as they viewed this as outside current standard care. Overall, HCPs felt that active monitoring was an unproven strategy in need of an evidence base; however, many acknowledged that active monitoring for low-risk DCIS could be appropriate for patients with significant co-morbidities or limited life expectancy. They believed that most patients would opt for surgery wherever possible. Conclusions: This study highlights the important need for robust randomised controlled trial data about active monitoring for women with low-risk DCIS, to provide HCPs with confidence in their management recommendations and decision-making. Highlights: First study to explore HCPs' in-depth views on active monitoring for low-risk DCIS. HCPs generally feel uncomfortable recommending active monitoring for low-risk DCIS. Active monitoring may be considered for patients with significant co-morbidities or limited life expectancy. Need for robust randomised controlled trial data on active monitoring for DCIS.